Energy Security Management of Poland and Western Europe In The Aspect of The Conflict in Ukraine - Przemyslaw SZOPA (Communications of International Proceedings, 2022)
The article presents the impact of the armed conflict between Russia and Ukraine upon energy security of Poland and Western European countries. The hostilities initiated geopolitical changes regarding the reduction of fuel (natural gas, crude oil) imports from Russia. The article analyzes the European energy policy which was implemented before the outbreak of the conflict and confronts its provisions with the new reality that emerged at the end of February 2022.  In addition, based on the research method, which is a study of the literature and an analysis of available source data, plans for changes regarding the reconstruction of the energy policy of Poland and Europe aimed at ensuring sustainable energy security through very ambitious, but also very demanding and long-term measures are presented. In the field of energy security management, economic, geopolitical and ecological aspects were mentioned.
Keywords: Energy Security; Consumption of Energy Resources; Energy Policy; Energy Management; Renewable Energy Sources